Gastrointestinal Stromal Tumors: Clinicopathology and Advances in Molecular Pathogenesis - Huang, MD, PhD, He; Chen, MD, PhD, Frank (North American Journal of Medicine and Science, 2012)
Gastrointestinal stromal tumors (GISTs) are common mesenchymal neoplasms in the gastrointestinal (GI) tract that need to be differentiated from other GI mesenchymal tumors. They often present with heterogeneous features based on the anatomic locations, histomorphology and gene mutation status, which may lead to diagnostic and treatment challenges. Over the past decade, numerous studies revealed that KIT and PDGFRα tyrosine kinase pathways play key roles in the molecular pathogenesis of GISTs. Subsequently, specific biomarkers, such as CD117 and DOG1, have been developed and greatly improved the diagnostic accuracy. Moreover, advances in understanding the molecular nature of GISTs also provide valuable therapeutic targets. Two tyrosine kinase inhibitors, Imatinib and Sunitinib, have currently been approved for treating patients with advanced and metastatic GISTs.